2016
DOI: 10.1002/2016jf003956
|View full text |Cite
|
Sign up to set email alerts
|

Rapid degradation of permafrost underneath waterbodies in tundra landscapes—Toward a representation of thermokarst in land surface models

Abstract: Waterbodies such as lakes and ponds are abundant in vast Arctic landscapes and strongly affect the thermal state of the surrounding permafrost. In order to gain a better understanding of the impact of small‐ and medium‐sized waterbodies on permafrost and the formation of thermokarst, a land surface model was developed that can represent the vertical and lateral thermal interactions between waterbodies and permafrost. The model was validated using temperature measurements from two typical waterbodies located wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 86 publications
0
87
0
Order By: Relevance
“…This outcome was a consequence of the physical processes that enhance thaw in sediments submerged beneath surface water. To our knowledge, these physics have been investigated extensively beneath larger lakes and ponds (e.g., Burn, , Ling, ; Langer et al, , ; Westermann et al, ) but have not been analyzed rigorously on spatial scales typical of a flooded polygonal trough. Fundamentally, we found that enhanced thaw beneath thermokarst pools was driven by a contrast between efficient downward transfer of energy in summer, and inefficient release of energy back to the atmosphere in winter (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…This outcome was a consequence of the physical processes that enhance thaw in sediments submerged beneath surface water. To our knowledge, these physics have been investigated extensively beneath larger lakes and ponds (e.g., Burn, , Ling, ; Langer et al, , ; Westermann et al, ) but have not been analyzed rigorously on spatial scales typical of a flooded polygonal trough. Fundamentally, we found that enhanced thaw beneath thermokarst pools was driven by a contrast between efficient downward transfer of energy in summer, and inefficient release of energy back to the atmosphere in winter (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Water bodies in permafrost regions cause the greatest (among all land cover classes) difference between ground temperatures and regional air temperatures, increasing sediment temperatures up to 10°C above the mean annual air temperatures and allowing permafrost under lakes to thaw, even in cold permafrost regions (Brewer, ; Jorgenson et al., ; Lachenbruch, Brewer, Greene, & Marshall, ; Smith, ). Models simulating the thermal disturbance caused by shallow (<1 m) ponds show thermokarst occurring four‐ to fivefold faster and 30–40 years earlier than the surrounding tundra (Langer et al., ). Thawing permafrost and destabilizing streambanks and riparian corridors could increase stream nutrients and sediment loads (Bowden et al., ; Kokelj et al., ), but beaver dams also attenuate these fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lake was only rarely covered and thus insulated by a complete snow cover and prone to strong snow drift. The significant heat fluxes during the frozen ice cover period stand in contrast to very small heat fluxes observed above tundra during this time of the year, where the soil and small ponds freeze completely and the subsurface heat reservoir is emptied quickly at the beginning of winter (Langer et al, ).…”
Section: Discussionmentioning
confidence: 99%